Resposta inflamatória em asininos (Equus asinus) submetidos à ovariectomia - Barros, Isabella de Oliveira (Universidade Federal Rural do Semi-Árido, 2016)
Acute phase proteins are glycoproteins produced by hepatocytes and released into the bloodstream in response to tissue damage resulting from acute inflammatory processes. Currently, they are considered biomarkers of inflammation or infection, compared with other variables such as hyperthermia, leukocytosis and neutrophilia, but in donkeys have not yet been analyzed. This study aimed to evaluate acute inflammatory response in donkeys submitted to ovariectomy by two different approaches. We randomly selected 18 adult females animals weighing on average 100 kg, which were divided into two groups: Group I, 9 animals were ovariectomized by laparotomy and group II, 9 animals by laparoscopy. After the surgeries were evaluated the following variables in whole blood: blood count, white blood cell count differential cell count, fibrinogen, haptoglobin, albumin, antitrypsin, alpha-1-acid glycoprotein, ceruloplasmin, transferrin, immunoglobulins A and G (acute phase proteins) . In the same time, the peritoneal fluid were measured: number of erythrocytes and leukocytes, cytological analysis differential (leukocytes and mesothelial cells), total protein, pH and acute phase proteins. All variables were analyzed before surgery, 12, 24, 48, 72 hours, 8 and 16 days after surgery. There was an increase (p <0.05) in the number of leukocytes with neutrophilia after surgery, regardless of the surgical serum and peritoneal procedure. Acute phase proteins had different behaviors in blood and peritoneal fluid. For the first time, we identified a P23.000kD protein in serum and peritoneal samples in donkeys. The interest on the role of acute phase proteins in the veterinary medicine, particularly in horses is growing, mainly aiming to use them as early markers of inflammation
Inflammatory response in donkeys (Equus asinus) submitted to ovariectomy
Keywords: Inflamação; Líquido peritoneal; Proteína de fase aguda; Jumentos; Inflammation; Peritoneal fluid; Acute phase proteins; Donkeys; CIENCIAS AGRARIAS::MEDICINA VETERINARIA